Expected Electoral Innovations: An Utterly Pressing ‘Democratization & Enfranchising’ Emergency in Political Landscape of Nepal (Samsad Journal संसद जर्नल, 2024)
Election is one of the key and cardinal events in the democracy, and it embodies huge ground of importance in multiple aspects. Conducting elections periodically in free, fair and fast manner is an inevitable and inexorable obligation of each nation. There is no room and reason to refute this onus. Ergo, timely changes and modifications in the election practices and provisions become an utmost and pressing emergency for all the nations in order to address the recent trends and mitigate the emerging electoral challenges. Nepal no longer is in zone of exception with this dire need of the universal similarity. This paper charts out two major issues a) inherent beauty of election, and b) couple of cardinal electoral innovations and major modifications that Nepal, as soon as possible, has to daringly commence to additionally democratize upcoming election activities in pursuit of commendable trust, prompt response, higher validity, larger attraction, supplementary resourcefulness, added enthusiasm, upheld optimism, and mass social audits from the public.